2020
DOI: 10.1038/s41598-020-63331-x
|View full text |Cite
|
Sign up to set email alerts
|

The establishment of neuron-specific enolase reference interval for the healthy population in southwest China

Abstract: To investigate and establish a reference interval (RI) of neuron-specific enolase (NSE) in southwest China's healthy population by using the laboratory information system database. A total of 86957 periodic health examination individuals of the medical examination center in West China Hospital from 2016 to 2018 were included in the study. We used the Box-Cox conversion combined with the Tukey method to normalize the data and eliminate the outliers, and the normal distribution method and the nonparametric metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…It is involved in the brain's glycolytic pathway of energy metabolism. It has been reported to be released from neurons especially during periods of injury and is currently considered a sensitive indicator of the severity of nerve cell injury and prognosis [86]. In this study, an increase in NSE reactivity was observed in groups administered methotrexate, suggesting a possible increase in neuronal injury which is consistent with our observations in the H and E stained sections of the dentate gyrus.…”
Section: Discussionsupporting
confidence: 91%
“…It is involved in the brain's glycolytic pathway of energy metabolism. It has been reported to be released from neurons especially during periods of injury and is currently considered a sensitive indicator of the severity of nerve cell injury and prognosis [86]. In this study, an increase in NSE reactivity was observed in groups administered methotrexate, suggesting a possible increase in neuronal injury which is consistent with our observations in the H and E stained sections of the dentate gyrus.…”
Section: Discussionsupporting
confidence: 91%
“…One must assume that the levels of S100B or NSE possibly correlate with individual factors such as genetic variants, race, geological location, and genotype, for instance (Ben Abdesselam et al 2003 ; Liu et al 2005 ; Miao et al 2020 ). Thus, such variants must be considered for the validation of biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…When the concentration comparison between other CKD groups is significantly different, and the results of the normal deviation test (z-test) indicate that the reference range needs to be set according to the subgroup, the corresponding upper reference limit of the subset is set. The formula for the z-test is as follows ( 13 ):…”
Section: Methodsmentioning
confidence: 99%